MINAT BELAJAR BERNYANYI PADA PEMBELAJARAN SENI BUDAYA DI KELAS VIII.2 SMP N 5 PARIAMAN - Dari, Wulan; Erfan, Erfan; Sudarman, Yos (SENDRATASIK UNP, 2019)
AbstractThis article aimed to determine the learning interest of students and factors that influence student interest in learning music art (singing) in SMP Negeri 5 Pariaman.This type of research was qualitative research with a descriptive approach. The main instrument in this study was the researchers themselves and assisted with supporting instruments such as stationery and cameras. Techniques of data collection were carried out by means of literature studies, interviews and documentation. The data were analyzed by looking at the results of observations and the results of interviews that had been conducted during the study.The results showed that there were two things that influenced the interest in learning singing in art and culture subject in 8th grade class of SMP N 5 Pariaman namely students’ internal and external factors. Internal factors include physical and psychological. External factors of students include the principal, teacher and parents. The lack of students' interest in learning the music art (singing) in SMP N 5 Pariaman is caused by the lack of strategies and methods used by teachers in the learning process. Whereas learning arts and culture (music) requires learning in the form of theory and practice in a balanced manner, to increase students' interest in learning in the art of music (singing).Keywords: Interest in study, singing, art and cultural learning